Efektivitas Program Rehabilitasi Sosial bagi Anak Jalanan di Kota Samarinda - Trisna Waty Riza Eryani; Konita Turaina; Firdayanti Ayu Nurunda; Ahmad Yani; Abdul Rofik; Muhammad Habibi (LPPM Institut Pendidikan Nusantara Global, 2026)
Street children are children aged 5–18 years who spend a significant portion of their time in public spaces, particularly on the streets. Samarinda, as the capital of East Kalimantan Province, continues to face complex social problems related to the presence of street children despite the existence of regulatory measures. Samarinda City Regional Regulation Number 7 of 2017 prohibits people from giving money to beggars, street children, and homeless individuals in public places. However, in practice, street children are still frequently found, especially at traffic intersections. This condition is influenced by several factors, including family economic pressure, limited rehabilitation facilities or shelters, and the influence of the street environment that encourages children to remain involved in street activities. This study aims to analyze the effectiveness of the social rehabilitation program implemented by the Samarinda City Office of Social Affairs and Community Empowerment in improving the behavior and living conditions of street children. This research employed a qualitative method with an exploratory approach. Data were collected through interviews, observations, and documentation, and analyzed using the interactive data analysis model proposed by Matthew B. Miles, A. Michael Huberman, and Johnny Saldana. The results show that the social rehabilitation program for street children in Samarinda is relatively effective. A total of 28 street children participated in vocational skills training such as welding, beauty services, cooking, and baking. These activities help change the mindset of street children and encourage them to engage in more productive activities. However, the program still faces several obstacles, including limited rehabilitation facilities, family economic pressure, and the influence of the street environment that often encourages children to return to street life.